Big Five Personality Traits as the Predictors of Creative Self‐Efficacy and Creative Personal Identity: Does Gender Matter?. (7th September 2013) - Karwowski, Maciej; Lebuda, Izabela; Wisniewska, Ewa; Gralewski, Jacek
Abstract: The aim of this study was to examine the relation of the Big Five personality factors to two self‐concept variables of growing importance in creativity literature: creative self‐efficacy (CSE) and creative personal identity (CPI). The analysis, conducted on a large ( N  = 2674, 49.6% women) and varied‐in‐age (15–59 years old) nationwide sample of Poles, using the structural equation model, demonstrated that personality factors are responsible for 23% of CSE and 21% of CPI variances. CSE and CPI were associated with all five personality dimensions: positively with Openness to Experience, Extraversion and Conscientiousness, negatively with Neuroticism and Agreeableness. The separate analyses conducted on men and women showed the differences among the predictors of CSE and CPI. Although Openness to Experience, Conscientiousness, and Neuroticism predicted CSE among both men and women, Extraversion was positively and Agreeableness negatively related to women's CSE. Conscientiousness was positively related to CPI only among men, and Agreeableness was negatively related to it only among women. Extraversion, Neuroticism, and Openness predicted CPI in the same manner among men and women.